Kebijakan Politik dan Keamanan Australia di Kawasan Asia Pasifik - Jemadu, Aleksius (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2006)
The main objective of this paper is to explain the evolution of Australias security and foreign policy in the Asia Pacific region. It is argued that the uniqueness of Australias position in this region affects both the content and modalities of its security and foreign policy vis a vis its Asian neighbours. Since PM John Howard took power, there has been a more assertive and aggressive approach towards the region as Australia tries to respond the changing environment of its national security policy. Australias security policy may affect its relationship with the Asian neighbours especially Indonesia in the sense that contention and friction may become a recurrent pattern. Both Australia and Indonesia should be aware of that reality and try to anticipate the consequences by referring to the existing opportunities for good neighbour policy.